2013
DOI: 10.4014/jmb.1307.07024
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Salt Stress Tolerance in Transgenic Potato Plants Expressing IbMYB1, a Sweet Potato Transcription Factor

Abstract: IbMYB1, a transcription factor (TF) for R2R3-type MYB TFs, is a key regulator of anthocyanin biosynthesis during storage of sweet potatoes. Anthocyanins provide important antioxidants of nutritional value to humans, and also protect plants from oxidative stress. This study aimed to increase transgenic potatoes' (Solanum tuberosum cv. LongShu No.3) tolerance to environmental stress and enhance their nutritional value. Transgenic potato plants expressing IbMYB1 genes under the control of an oxidative stress-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 55 publications
(65 reference statements)
0
35
0
Order By: Relevance
“…It was reported that in MYB-overexpressing transgenic Arabidopsis plants, the over-accumulation of anthocyanin was directly associated with oxidative and drought tolerance (Nakabayashi et al 2014). Transgenic potato plants overexpressing IbMYB1 showed high amounts of secondary metabolites, and had higher salt tolerance than non-transgenic plants (Cheng et al 2013). A few R2R3-MYB proteins, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that in MYB-overexpressing transgenic Arabidopsis plants, the over-accumulation of anthocyanin was directly associated with oxidative and drought tolerance (Nakabayashi et al 2014). Transgenic potato plants overexpressing IbMYB1 showed high amounts of secondary metabolites, and had higher salt tolerance than non-transgenic plants (Cheng et al 2013). A few R2R3-MYB proteins, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several wheat R2R3-MYBs, including TaMYB1 (Lee et al 2007), TaMYB2A (Mao et al 2011), TaMYB33 (Qin et al 2012, TaMYB73 ), TaMYB30-B (Zhang et al 2012a, were shown to improve stress tolerance in transgenic plants, respectively. MYB proteins were also reported to be involved in the flavonoid biosynthesis in many plant species (Cheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, flavonols are compounds with high antioxidant activity, and the upregulation of their biosynthesis increased protection against UV radiation in Ligustrum vulgare plants [16]. Potato plants overexpressing transcription factor IbMYB1 exhibited enhanced anthocyanin production and improved salinity tolerance [17]. Anthocyanin biosynthetic genes PAL and CHS are proposed as candidates for molecular breeding to increase crop resistance to wounding and salt stress [18].…”
Section: Introductionmentioning
confidence: 99%
“…Transgenics preserved higher water content and had over twice the dry weight of NTs (Ahmad et al, 2008). In another study of the same group, COD-transformant potato plants showed higher antioxidant enzyme activity, better photosynthetic efficiency, higher chlorophyll content, and lower MDA content than NTs under drought stress conditions (Cheng et al, 2013). Introduction of the yeast TREHALOSE-6-PHOSPHATASE SYNTHASE1 (TPS1) gene, which functions in the biosynthesis of osmolyte trehalose, into potato leads to drought tolerance by increasing the relative water content in source tissues (leaves) (Kondrák et al, 2012), and by enhancing the accumulation levels of amino acids such as glutamine, glutamate, phenylalanine, proline, and asparagine in sink tissues (tubers), indicating a partial difference in tolerance mechanisms against drought stress in source and sink organs (Juhász et al, 2014).…”
Section: Transgenics Of Drought and Heat Tolerance In Potatomentioning
confidence: 92%
“…Several droughtresponsive genes including AtHB-7, RD28, ALDH22a1, and ERD1-like were induced in transgenic plants under drought conditions, suggesting that StMYB1R-1 functions as a transcription factor involved in the activation of drought-related genes. In a similar study, the Ipomoea batatas (sweet potato) IbMYB1 gene, an R2R3-type MYB transcription factor involved in secondary metabolite production, was overexpressed in potato (Cheng et al, 2013). Transgenic potato plants could tolerate the drought since they accumulated higher levels of secondary metabolites such as phenols, flavonoids, and anthocyanin.…”
Section: Transgenics Of Drought and Heat Tolerance In Potatomentioning
confidence: 99%